SOSIALISASI PENINGKATAN KOMPETENSI PEMBELAJARAN MATA KULIAH AKUNTANSI MASA PANDEMI COVID 19 TERHADAP MAHASISWA/I DI WILAYAH JABODETABEK - IGP RatihAndaningsih, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
This research analyses development of e learning facility with Online sytem Of Accounting .Improving the quality and learning quality of accounting courses is one of the efforts made to improve student competence.this study aims to better understand the online lecture learning system by using an integrated online system in financial accounting and management accounting courses in increasing skills and knowledge for students in the Greater Jakarta area and surrounding areas.This qualitative descriptive study uses the content method with 20 respondents and the results of long distance interviews from student representatives in the Greater Jakarta Area.It is hoped that this researchwill result in an increase in quality and competence on post pandemic Covid 19 to students in e learning process online integration system.The limitation of this research is the impact of elearningonline system of financial accounting and management accounting subject.The contribution of this research is that business Financial accounting and business administration’s student in Accounting majoring are able to maintain skill and knowledge